2020
DOI: 10.1111/jfbc.13280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Andrographis paniculata leaves extract on neurobehavioral and biochemical indices in scopolamine‐induced amnesic rats

Abstract: The brain plays a major role in the central nervous system (CNS) and an important organ of the body that controls the functions of all other organs with the aid of neurons through signal transmission, whereas, in neurodegeneration, the functions of these neurons are impaired or altered (Ortman, Velkoff, & Hogan, 2014). Neurodegeneration is a process that refers to any pathology that mainly affects the neurons gradually. This condition alters the structure and function of neurons which leads to increased neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Their effect on BChE was diverse: GAL and CCN slightly decreased it, 4b LD slightly increased it and 4b HD had no effect. SC increased both AChE and BChE activities as it was observed by others [ 8 , 27 ].…”
Section: Discussionsupporting
confidence: 84%
“…Their effect on BChE was diverse: GAL and CCN slightly decreased it, 4b LD slightly increased it and 4b HD had no effect. SC increased both AChE and BChE activities as it was observed by others [ 8 , 27 ].…”
Section: Discussionsupporting
confidence: 84%
“…There is mounting evidence of the biological functions of AP, such as anticancer, anti-inflammatory, antimalarial, antimicrobial, antioxidant, cardioprotective and immunomodulatory activities (35)(36)(37), but not of its role in estrogen deficiency-related osteoporosis. Our study results verified the characteristics of accelerated bone loss in OVXinduced estrogen deficiency-related osteoporotic mice and showed that it could be counteracted by AP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptide is documented to be associated with reactive oxygen species’ generation, leading to the aggregation of Aβ and plaque formation [ 70 ]. Oxidative stress elicits lipid peroxidation, together with decreased GSH and antioxidant enzymes, which leads to cholinergic neuronal damage and cognitive dysfunctions [ 71 ]. Oxidative stress is among the fundamental mechanisms of cell damage following the administration of Scop [ 72 ].…”
Section: Discussionmentioning
confidence: 99%